Ilmu Kalam Yang Dicela Imam Shafi'i - Ahmad Baha Mokhtar; Abdul Muthalif Afuwardeen; Ahmad A'toa' Mokhtar; Ahmad Najaa' Mokhtar (Universiti Islam Sultan Sharif Ali, Gadong, Brunei, 2024)
Non-Indexed Publication